Gut Microbiota as Emerging Players in the Development of Alcohol-Related Liver Disease - Wei Li; Wenkang Gao; Shengqi Yan; Ling Yang; Qingjing Zhu; Huikuan Chu (Biomedicines)
The global incidence and mortality rates of alcohol-related liver disease are on the rise, reflecting a growing health concern worldwide. Alcohol-related liver disease develops due to a complex interplay of multiple reasons, including oxidative stress generated during the metabolism of ethanol, immune response activated by immunogenic substances, and subsequent inflammatory processes. Recent research highlights the gut microbiota’s significant role in the progression of alcohol-related liver disease. In patients with alcohol-related liver disease, the relative abundance of pathogenic bacteria, including Enterococcus faecalis, increases and is positively correlated with the level of severity exhibited by alcohol-related liver disease. Supplement probiotics like Lactobacillus, as well as Bifidobacterium, have been found to alleviate alcohol-related liver disease. The gut microbiota is speculated to trigger specific signaling pathways, influence metabolite profiles, and modulate immune responses in the gut and liver. This research aimed to investigate the role of gut microorganisms in the onset and advancement of alcohol-related liver disease, as well as to uncover the underlying mechanisms by which the gut microbiota may contribute to its development. This review outlines current treatments for reversing gut dysbiosis, including probiotics, fecal microbiota transplantation, and targeted phage therapy. Particularly, targeted therapy will be a vital aspect of future alcohol-related liver disease treatment. It is to be hoped that this article will prove beneficial for the treatment of alcohol-related liver disease.